IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PJOK DITINJAUH DARI TAHAP PERENCANAAN DIKECAMATAN LOKSADO - Rijaldi, Rijaldi; Rakhman, Arie; Mulhim, Muhammad (Universitas Hamzanwadi, 2024)
Abstract The independent curriculum provides freedom to export the abilities and interests of students. The quality of education is impacted by changes in government policy regarding the educational system in both positive and bad ways. The purpose of this study is to determine how the autonomous curriculum is implemented by examining the teachers' comprehension of creating instructional materials for various module types. This research method uses quantitative descriptiveness. The research instrument uses questionnaires that are in accordance with the indicators of the teaching module. With the research subject of PJOK teachers in Loksado sub-district with purposive sampling techniques with the first keriteria, schools that implement an independent curriculum. Quantitative research data is analyzed in percentage form. The average result of all indicators in the implementation of the independent curriculum on suitability in making teaching equipment has a result of 63.6% and it can be concluded that educators in Loksado sub-district have a fairly high understanding based on percentage results. There are 3 components of the teaching module, namely, General information gets a percentage of 66.5% at the indicator stage of determining the learning model is at a fairly high number, namely 71% of teachers can be said to be familiar with determining a learning model while for the lowest indicator, namely in facilities and infrastructure 50%, in the Core Component it gets a percentage of 63.15% and the highest indicator, which is at the stage of determining learning objectives based on CP analysis, has The high percentage is 71%, while the lowest indicator is the reflection indicator 54% and then in the Appendix the results of the questionnaire are at 60.3%, the highest indicator is found in making Student Worksheets showing a percentage of 62.5%. Keywords: Implementation, Independent Curriculum, Corner Learning, Planning